Epidemiology of hanseniasis cases notified in Guaraí, Tocantins, from 2008 to 2018 - Dias, Adriana Keila; Américo-Pinheiro, Juliana Heloisa Pinê; Lima, Leonice Domingos dos Santos Cintra; Frias, Danila Fernanda Rodrigues (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The present work aimed to analyze the epidemiological data of leprosy available in public domains from 2008 to 2018 in the municipality of Guaraí, Tocantins. This is a cross-sectional, descriptive, retrospective and quantitative study based on secondary data. In the period from 2008 to 2018, 328 cases of leprosy were registered with a coefficient of general hyperendemic detection in the years 2008, 2009 and 2012, very high in 2010 and 2013, high in 2011, 2014, 2015, 2016, and 2017; especially 35-49 years old with 96 (29%) cases, 20–30 and 50-64 with 78 (24%) respectively. The mean detection rate of the disease in children under 15 years of age during the study period was 6.7 / 100,000 inhabitants, with 50.3% of cases classified as paucibacillary and 49.7% multibacillary. Given the above, the need for measures that reveal the epidemiological reality of leprosy is reinforced, raising aspects that may contribute to prevention, diagnosis and treatment, in order to reduce morbidity and physical disabilities.